The influence of financial literacy, money attitude, financial strain and financial capability on young employees' financial well-being - Sabri, Mohamad Fazli; Zakaria, Nurul Farhana (Universiti Putra Malaysia Press, 2015)
The rising cost of living and difficult economic conditions have made Malaysian individuals and households more conscious of their financial management. This study aims to (1) identify the levels of financial literacy, financial strain, financial capability and financial well-being and the type of money attitude of young Malaysian employees; (2) explore the differences in financial well-being based on the demographic characteristics of young employees; (3) analyse the relationships between the financial well-being of young employees and their financial literacy, money attitude, financial strain and financial capability; and (4) identify the determinants of financial well-being among young employees. The sample for this study consisted of 508 young employees in the public and private sectors aged 40 years and below from four urban areas in central Peninsular Malaysia, who were selected through the multi-stage sampling technique. Data were collected through self-administered questionnaires. The findings indicate that respondents who had moderate levels of financial literacy, financial capability and financial well-being scored high in effort and retention money attitudes and had a low level of financial strain. Statistically significant differences emerged in the financial well-being of those of different marital status (married and single) and the different household income groups (lower, middle and high-income), while there were significant relationships between financial well-being and financial literacy, type of money attitude, financial strain and financial capability. Demographic characteristics (gender and monthly household income), financial literacy, retention-money attitude, effort-money attitude, financial strain and financial capability had significant influence on financial well-being with financial strain being a major factor contributing to financial well-being.